Jogos e brincadeiras africanas e afro-brasileiras no contexto da educação para as relações étnico-raciais: guia de ações didático-metodológicas para as aulas de Educação Física - SANTOS, Hugo Victor Silva (2024)
This study aims to verify how education for ethnic-racial relations is implemented under the light of Law 10.639/06 at a state school in São José de Ribamar (MA), using the thematic unit of games and activities in Physical Education. The research was guided by the following questions: how does the Physical Education teacher for the 8th and 9th grades at the specified school incorporate African and Afro-Brazilian games and activities to promote the identity formation and respect of black children, and what are the main challenges faced in this process? It's an applied, qualitative research was conducted through educational intervention at the Centro de Ensino Dr. Tarquínio Lopes Filho. The theoretical foundation included studies of laws and guidelines for the appreciation of African and Afro-Brazilian history and culture, such as Law No. 10.639 of 2003, the National Education Guidelines and Framework Law, the National Common Curricular Base, the National Curriculum Parameters, and the Maranhão Territorial Curriculum Document, as well as scientific works published in the Conbrace and ANPEd annals, and authors discussing the role of games and activities in the context of Ethnic-Racial Relations. Data collection instruments included non-participant observation followed by a semi-structured interview conducted with the principal and a Physical Education teacher at the specified school, and the responses revealed an absence of African/Afro-Brazilian/Afro-Maranhense cultural elements both in the curriculum and in Physical Education practices. It was understood that, given the invisibility of these elements in Physical Education teaching and the lack of appropriate materials, the Final Product, the Didactic-Methodological Action Guide for Physical Education classes, can contribute to ethnic-racial education at the study school.